2019
DOI: 10.1101/560300
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spt6 is a maintenance factor for centromeric CENP-A

Abstract: Replication and transcription of genomic DNA requires partial disassembly of nucleosomes to allow progression of polymerases. This constitutes both an opportunity 2 to remodel the underlying chromatin as well as the potential danger of losing epigenetic information. Centromeric transcription has been shown to be required for stable incorporation of the centromere-specific histone dCENP-A in M/G1-phase, which depends on the eviction of previously deposited H3/H3.3-placeholder nucleosomes.Here we demonstrate tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 91 publications
(137 reference statements)
1
12
0
Order By: Relevance
“…Direct evidence came from work in mammalian cell lines and Xenopus oocyte extracts where knock-down of centromeric transcripts resulted in reduced CENP-A levels at the centromere [ 21 , 24 , 25 , 26 , 33 , 48 ]. Indeed, recent work in mammalian and fruit fly cell lines showed that chemical inhibition of activated RNAP2 resulted in the loss of centromeric CENP-A CID chromatin [ 21 , 52 ]; and the elongation factor Spt6 facilitates maintenance of centromeric CENP-A CID [ 105 ]. These lines of investigation strongly hint at a distinct role for both the act of transcription and the production of an RNA species in the loading of CENP-A.…”
Section: Functions Of Centromeric Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct evidence came from work in mammalian cell lines and Xenopus oocyte extracts where knock-down of centromeric transcripts resulted in reduced CENP-A levels at the centromere [ 21 , 24 , 25 , 26 , 33 , 48 ]. Indeed, recent work in mammalian and fruit fly cell lines showed that chemical inhibition of activated RNAP2 resulted in the loss of centromeric CENP-A CID chromatin [ 21 , 52 ]; and the elongation factor Spt6 facilitates maintenance of centromeric CENP-A CID [ 105 ]. These lines of investigation strongly hint at a distinct role for both the act of transcription and the production of an RNA species in the loading of CENP-A.…”
Section: Functions Of Centromeric Transcriptionmentioning
confidence: 99%
“…It is not very likely that new CENP-A is loaded exclusively on naked DNA, rather than on chromatin. Indeed, in human and fruit fly cell lines, active transcription is needed to remove so-called placeholder H3.3 nucleosomes prior to new CENP-A loading at the centromere [ 53 , 105 , 106 ]. Similarly, in fission yeast, H3 nucleosomes function as placeholder nucleosomes [ 61 ].…”
Section: Functions Of Centromeric Transcriptionmentioning
confidence: 99%
“…Interestingly, the Spt6-RNAPII association is required for efficient recruitment of the Ccr4-Not mRNA-processing and deadenylation complex [ 132 ]. It was recently shown, in both Drosophila and human cells, that Spt6 is directly involved in CEN transcription and CENP-A maintenance [ 133 ]. Spt5 contributes to the recruitment of the mRNA capping enzyme [ 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…General components of the transcription machinery such as the POLR2B, a subunit of RNA polymerase II and CDK9 P-TEFb , a critical kinase in the transcription elongation complex (Cho et al, 2010) also impact on CENP-A maintenance as well as assembly (for POLR2B). Pleiotropic effects of depleting these general transcription-related proteins cannot be excluded but nevertheless these factors are of interest as a direct role for transcription in CENP-A maintenance and assembly has been suggested (Bobkov et al, 2019(Bobkov et al, , 2018Bergmann et al, 2011).…”
Section: Common Themes Among Factors Involved In Cenp-a Maintenancementioning
confidence: 99%